La presentación del psicoanálisis como una ciencia no-prototípica y revolucionaria en la obra de Freud - Flores Galindo Rivera, Pablo Miguel (2016)
This study analyzes the way in which Freud presents psychoanalysis as a science. From the review of the published work of Freud we would select and analyze the most important passages on the subject. Through this analysis we would be able to show that Freud presents psychoanalysis as a non-prototypical revolutionary science. We will show how Freud describes important features of his notion of psychoanalysis and its notion of science and that the fact that Freud present psychoanalysis as science does not necessarily refer to the clinical practice but rather to theoretical research.